Effect of Particulate Matter 2.5 on Fetal Growth in Male and Preterm Infants through Oxidative Stress - Sunwha Park; Eunjin Kwon; Gain Lee; Young-Ah You; Soo Min Kim; Young Min Hur; Sooyoung Jung; Yongho Jee; Mi Hye Park; Sung Hun Na; Young-Han Kim; Geum Joon Cho; et al. (MDPI AG, 2023)
Particulate matter 2.5 (PM2.5) levels are associated with adverse pregnancy outcomes. In this retrospective cohort study, we examined whether the concentration of indoor PM2.5 affected pregnancy outcomes. Additionally, we evaluated biomarkers of pregnancy-related complications caused by fine dust. We collected clinical information and data based on residential addresses from the Air Korea database to assess PM2.5 exposure levels. As a multicenter prospective cohort study, we measured the indoor PM2.5 concentration and inflammatory and oxidative stress markers. The PM2.5 concentration of the low-birth-weight (LBW) delivery group was 27.21 μg/m3, which was significantly higher than that of the normal-birth-weight (NBW) group (26.23 μg/m3) (p = 0.02). When the newborns were divided by sex, the PM2.5 concentration of the LBW group was 27.89 μg/m3 in male infants, which was significantly higher than that of the NBW group (26.26 μg/m3) (p = 0.01). In the prospective study, 8-hydroxy-2-deoxyguanosine significantly increased in the high-concentration group (113.55 ng/mL, compared with 92.20 ng/mL in the low-concentration group); in the high-concentration group, the rates of preterm birth (PTB) and small size for gestational age significantly increased (p < 0.01, p = 0.01). This study showed an association between PM2.5, oxidative stress, and fetal growth, with the PTB group being more vulnerable.